THE ROLE OF WOMEN ENTREPRENEURS IN SUPPORTING SUSTAINABLE DEVELOPMENT GOALS (SDGs) THROUGH HALAL MSMES IN INDONESIA - AMELIA, RIKA (Lentera : Journal of Gender and Children Studies, 2025)
Women entrepreneurs in MSMEs are increasingly recognized for their role as drivers of the national economy and important contributors to supporting the achievement of the Sustainable Development Goals (SDGs), particularly those related to poverty alleviation, gender equality, and sustainable economic growth. This study aims to analyze how women entrepreneurs in halal MSMEs contribute to accelerating the achievement of the SDGs in Indonesia. The method used was library research, reviewing various scientific literature, official institutional reports, and government regulations relevant to Islamic economic issues and the role of women in MSMEs. The results show that women entrepreneurs not only play a role as drivers of the family economy but also as agents of social development by creating new jobs, strengthening local economic resilience, and increasing community halal literacy. Halal MSMEs have been shown to have high levels of consumer trust and resilience to crises, but they still face obstacles such as access to capital, digital literacy, and minimal support for gender-based affirmative policies. In conclusion, strengthening the capacity of women in the halal MSME ecosystem is an effective and strategic strategy to support the acceleration of the SDGs in an inclusive and sustainable manner. Keywords: Women Entrepreneurs; Halal MSMEs; and SDGs.